Macro Volatility and Financial Crisis in Thailand : Some Historical Evidence - Pholphirul, Piriya (2012)
This paper uses national income identity to explain the causal relationships among Thailand's aggregate volatility, deficient financial structure, financial liberalization, and financial crisis in this country. Relatively good macroeconomic policies and diversified structure were able to compensate for financial imperfections and weak corporate governance in the financial sector in the period 1970-90. Under these conditions, real GDP growth was positive, inflation was relatively low, and consumption was relatively less volatile than GDP. The 1997 crisis, however, severely affected the ability of central authorities to smooth fluctuation. Investment and consumption volatility increased substantially. This implies that, when counter-cyclical policies are difficult to implement and incomplete markets exist, it is much more difficult to stabilize consumption.